2022
DOI: 10.1007/s12371-022-00716-6
|View full text |Cite
|
Sign up to set email alerts
|

Geodiversity Assessment of French Guiana: Challenges and Implications for Sustainable Land Planning

Abstract: As operational concept, geodiversity implies a measurement and its application narrowed to a given spatial area, allowing the identification of clusters for prioritization and planning purposes. This study proposes a first geodiversity index assessment for French Guiana, a French Oversea territory located within the Guiana Shield (South America). Almost entirely covered by the Amazon rainforest associated with an exceptional biodiversity, French Guiana appears as an international conservation and land-planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…To characterise this relationship, absolute changes from the ES1000 to the ES50 maps in the ESs levels aggregated according to landforms, land uses or municipalities are plotted against similar absolute changes in pedodiversity (Figure 6a–d). As suggested in other studies (Scammacca et al, 2022), Figure 6 clearly shows quantitatively that changes in pedodiversity do not induce direct, simple or systematic changes in ESs levels. Several interesting behaviours may however be recognised.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To characterise this relationship, absolute changes from the ES1000 to the ES50 maps in the ESs levels aggregated according to landforms, land uses or municipalities are plotted against similar absolute changes in pedodiversity (Figure 6a–d). As suggested in other studies (Scammacca et al, 2022), Figure 6 clearly shows quantitatively that changes in pedodiversity do not induce direct, simple or systematic changes in ESs levels. Several interesting behaviours may however be recognised.…”
Section: Discussionsupporting
confidence: 82%
“…As suggested in other studies (Scammacca et al, 2022), Figure 6 clearly shows quantitatively that changes in pedodiversity do not induce direct, simple or systematic changes in ESs levels. Several interesting behaviours may however be recognised.…”
Section: Soil Typology and Soil Functionalitysupporting
confidence: 80%
“…As per the geodiversity theory of Gray (2013) , the inventories and characterisation of the KKGp can be classified through fossils, landforms, landscapes, rocks, and minerals. The classification methods ( Ruban, 2010 ; Neches, 2016 ; Ponjiger et al., 2021 ; Pal and Albert, 2021 ; Ferrando et al., 2021 ; Dias et al., 2021 ; de Paula Silva et al., 2021 ; Chrobak et al., 2021 ; Scammacca et al., 2022 ; Carrion-Mero et al., 2022 ) suggest that these geosites have potential as paleontological, geomorphological, stratigraphical, petrological, and mineralogical sites.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the geodiversity index map, it is most likely that suitable geosites can be found in the AOB, the cratons, and along the areas with high hydrological diversity in the sub-Andean foreland basins, the Solimões and Amazonas sedimentary basins. However, it is important to note that a previous study noticed that areas that ranked low in geodiversity were still of high ecological interest due to important lithological and geomorphological features found there [35]. Thus, simply using a grid-based approach is insufficient, and it is advised to combine a grid-based method using the approach as suggested by Brilha [19], which can be regarded as a qualitative-quantitative method as proposed by Zwolinski et al [175].…”
Section: (C) Methodological Challengesmentioning
confidence: 99%
“…Only few papers have described the geodiversity in the ADB until now, including four papers that discuss geodiversity in the Amazon, namely on the 'Amazônia legal' in Brazil [37] (the northern states of Brazil, including Mato Grosso and the west of Maranhão), the Xingu river basin [38], French Guiana [35] and the NAPO Sumaco (aspiring UNESCO) Geopark [53] (figure 1). De Andrade et al [37] conducted an extensive literature study of geodiversity in the 'Amazônia legal' and concluded that there is still little known about geodiversity in this region, neither is there information on a detailed scale.…”
Section: (A) Previous Geodiversity Studies In the Amazon Drainage Basinmentioning
confidence: 99%